Coexpression of BMI-1 and EZH2 Polycomb Group Genes in Reed-Sternberg Cells of Hodgkin’s Disease - Raaphorst, Frank M. (American Society for Investigative Pathology, 2000)
The human BMI-1 and EZH2 polycomb group (PcG) proteins are constituents of two distinct complexes of PcG proteins with gene regulatory activity. PcG proteins ensure correct embryonic development by suppressing homeobox genes, and they also contribute to regulation of lymphopoiesis. The two PcG complexes are thought to regulate different target genes and probably have different tissue distributions. Altered expression of PcG genes is linked to transformation in cell lines and induction of tumors in mutant mice, but the role of PcG genes in human cancers is relatively unexplored. Using antisera specific for human PcG proteins, we used immunohistochemistry and immunofluorescence to detect BMI-1 and EZH2 PcG proteins in Reed-Sternberg cells of Hodgkin’s disease (HRS). The expression patterns were compared to those in follicular lymphocytes of the lymph node, the normal counterparts of HRS cells. In the germinal center, expression of BMI-1 is restricted to resting Mib-1/Ki-67(−) centrocytes, whereas EZH2 expression is associated with dividing Mib-1/Ki-67(+) centroblasts. By contrast, HRS cells coexpress BMI-1, EZH2, and Mib-1/Ki-67. Because HRS cells are thought to originate from germinal center lymphocytes, these observations suggests that Hodgkin’s disease is associated with coexpression of BMI-1 and EZH2 in HRS cells.